Discourses on Downsizing: Structure and Sentiment in an Organizational Dispute - DeRoche, Constance (Anthropologica, 2022)
Downsizing, sometimes accompanied by staff amalgamation, has become a grim but pervasive cost-cutting device in Western societies of the 1990s. This article focusses on two hospital-based nursing schools, in an economically marginal Maritime community, that faced merger and the loss of a number of much-prized teaching jobs in the early 1990s. Although both staffs approved, in principle, of raising educational standards for nursing employment, they held distinctly different positions on how educational qualifications should figure in the layoff formula. Downsizing provoked a discourse that unveiled the significance of interpersonal loyalties and work group identities.